Culturally Sensitive Dimensions of Subjective Wellbeing Linked to Objective Measures: A Narrative Review - Joy M. Rooney (International Journal of Environmental Research and Public Health, 2026)
Background: Subjective wellbeing frameworks are widely used to determine individual and collective holistic dimensions of wellness. Increasingly, they may be linked to objective measures for use in government wellbeing policy-making across the world, although their cultural sensitivity is questioned. Methods: Fifty-nine peer-reviewed studies published between 2000 and 2026 were identified following Boolean searches in open access journals, screened, and quality assessed. Translated Western-English frameworks of seven authorities were compared, as were those ten within indigenous cultural groups. Ten other studies for consideration included objective and cultural dimensions. The remainder were used in background and synthesis presentation. Results: Five themes were distinguished: use of solid theoretical background; conceptual rationale for framework; methodological limitations; links, convergence, divergence, and contradictions; conceptual rationale for interpretation of related findings and theoretical considerations. Within a cultural group, even with great care in translation, and semantic amendments, most authorities’ dimensions of wellbeing models were questioned. Many interesting and adequate indigenous frameworks need invariance and longitudinal testing. Studies including quantitative objective measures of wellbeing more clearly defined unique cultural group effects within their environments. Conclusions: Dimensions of wellbeing need to be created, validated and reliably evaluated within the cultural groups they are intended to be used, rather than using translations. Much more quantitative research is needed with lay-consultation before, during, and following longitudinal studies.